Drought resilient Flemingia semialata Roxb. for improving lac productivity in drought prone ecologies - Ghosh, J.; Lohot, V. D.; Ghosal, S.; Singhal, V.; Sinha, N. K. (The Indian Journal of Genetics and Plant Breeding, 2017)
A drought tolerant line of Flemingia semialata (FS-S) has been identified from natural population as a better host plant for kusmi lac production and summer sustainability. FS-S had significantly higher fresh biomass, dry matter, broodlac and scraplac than local line (FS-L). Photosynthetic rate and stomatal conductance were also higher in FS-S line and it was fertilizer responsive too. It is more efficient in starch degradation than the local line which ultimately supports lac insect development. The high level of total sugar maintained by FS-S line is due to high chlorophyll content including carotenoid. Ascorbate peroxide and catalase (biochemical indicators for draught tolerance) was also higher in selected line